Determinants of Postpartum Depression In Rural Area, Central Java, Indonesia - Estiningtyas; Anindhita Yudha Cahyaningtyas (Journal of Health Science and Prevention, 2021)
Postpartum Depression (PPD) is a severe complication of labour result in an adverse effect on maternal and neonatal health. Nevertheless, the factors associated with postpartum depression are very rarely examined during postpartum care. This study aimed to discover the determinants of postpartum depression among mothers in a rural area, Central Java, Indonesia. The design of the study was observational analytic with a cross-sectional approach. The setting of the study was in Sukoharjo Regency. Participants of the study were 160 mothers, ages 20-35 years old, during 0-8 weeks of postpartum that were taken using a purposive sampling technique. The participants were given two questionnaires: (1) questionnaire on the socio-demographic; and (2) the Edinburgh Postpartum Depression Scale (EPDS) questionnaire. The questionnaires were distributed to mothers’ at their houses by the interviewers. The result findings shows that the determinants of postpartum depression are occupations (p=0.012), husband support (p=0.010), family support (p=0.027), social support (p=0.025), pregnancy planning (p=0.025), monthly income (p=0.021). PPD is not associated with age (p=0.417), parity (p=0.977), and level of education (p=0.892). Key conclusion: maternal mental health services need to be addressed in the management of the risk factors to prevent the occurrence of postpartum depression. Keywords: husband support, family support, social support, postpartum depression symptoms